Research on Intelligent Evaluation Model of Railway Internationalized Earthquake Emergency Rescue Talents Based on Analytic Hierarchy Process and Fuzzy Theory - Jin Jing; Yang Yu; Jiang Yuxin (Shock and Vibration)
Earthquakes occur frequently in the 21st century and cause a large number of casualties; induced secondary geological disasters will cause more serious casualties. How to reasonably deal with the earthquake disaster to carry out emergency rescue work is becoming increasingly urgent; the ability level of earthquake disaster emergency rescue personnel is directly related to the follow-up relief effect. Based on this, aiming at the emergency rescue ability of nationalized railway management talents in high-intensity earthquake areas around the world, this paper will use the methods of analytic hierarchy process and fuzzy theory to construct an intelligent evaluation model of railway international earthquake emergency rescue personnel ability. In addition, this paper carries out a questionnaire survey of experts in related fields and model empirical research and puts forward optimization measures and suggestions for the personnel training of railway international earthquake emergency rescue in high-intensity seismic areas based on the results of model evaluation.